Cold-mode and hot-mode accretion in galaxy formation: an entropy approach. Issue 3 (6th July 2022) - Tollet, E; Cattaneo, A; Macciò, A V; Kang, X
ABSTRACT: We have analysed two cosmological zoom simulations with M_vir10^12 M_ from the Numerical Investigation of a Hundred Astrophysical Objects (NIHAO) series, both with and without feedback. We show that an entropy criterion based on the equation of state of the intergalactic medium can successfully separate cold- and hot-mode accretion. The shock-heated gas has non-negligible turbulent support and cools inefficiently. In the simulations without feedback, only a small fraction (≲20 per cent) of the stellar mass comes from baryons that have been in the hot circumgalactic medium, although quantitative conclusions should be taken with caution due to our small-number statistics. With feedback, the fraction is larger because of the reaccretion of gas heated by supernovae, which has lower entropies and shorter cooling times than the gas heated by accretion shocks. We have compared the results of NIHAO to predictions of the GalICS 2.1 semi-analytic model of galaxy formation. The shock-stability criterion implemented in GalICS 2.1 successfully reproduces the transition from cold- to hot-mode accretion.